Harms from a partner’s drinking: an international study on adverse effects and reduced quality of life for women - Callinan, S.; Rankin, G.; Room, R.; Stanesby, O.; Rao, G.; Waleewong, O.; Greenfield, T.; Hope, A.; Laslett, Anne-Marie (2018)
Background: Partners of heavy drinking individuals can be detrimentally affected as a result of their partner’s drinking. Objectives: The aim of this study was to identify the proportion of heterosexual intimate partner relationships with a heavy drinking male that resulted in reported alcohol-related harm and to investigate the impact of this on well-being in 9 countries. Methods: This study used survey data from the Gender and Alcohol’s Harm to Others (GENAHTO) Project on Alcohol’s Harm to Others in 9 countries (10,613 female respondents, 7,091 with intimate live-in partners). Respondents were asked if their partners drinking had negatively affected them as well as questions on depression, anxiety, and satisfaction with life. Results: The proportion of partnered respondents that reported having a harmful heavy drinking partner varied across countries, from 4% in Nigeria and the US to 33% in Vietnam. The most consistent correlate of experiencing harm was being oneself a heavy episodic drinker, most likely as a proxy measure for the acceptability of alcohol consumption in social circles. Women with a harmful heavy drinking partner reported significantly lower mean satisfaction with life than those with a partner that did not drink heavily. Conclusions: Harms to women from heavy drinking intimate partners appear across a range of subgroups and impact on a wide range of women, at least demographically speaking. Women living with a heavy drinking spouse experience higher levels of anxiety and depression symptoms and lower satisfaction with life.